Analysis of Smoked Fish Processed Businesses on the Welfare of Coastal Communities in Lahewa District, North Nias District - Gulo, Ahmad Jumadin; Lubis, Irsad (LPPM UIKA Bogor, 2024)
Management of marine resources is still traditional, and community knowledge that can only be passed down from generation to generation has caused the people in Siheneasi Village to go into a cycle of poverty. The many daily needs exacerbate this condition, including children's education costs, health, and others. Living conditions still need to be fully controlled by society itself. In other words, life is still not sufficient. Sufficient in terms of children's education, health, and even daily costs. The mediocre income relies on results from the sea, which are sometimes uncertain, and unpredictable weather conditions that prevent coastal communities in Siheneasi Village from going to sea because they fear the high risks. This research aims to find out whether potential, capital, consumption, distribution, labor, technology, income, and education have a significant effect on increasing the welfare of coastal communities in Lahewa District and to find out relevant factors that have a significant influence on increasing the welfare of coastal communities in Lahewa District. What was studied was whether potential, capital, consumption, distribution, labor, technology, income, and education significantly influenced the welfare of coastal communities in Lahewa District and relevant factors significantly influenced the welfare of coastal communities in Lahewa District. A total sample of 207 respondents was collected by distributing questionnaires and processing data using Confirmatory Factor Analysis (CFA) and Multiple Linear Regression. The results of the Confirmatory Factor Analysis (CFA) test in the KMO and Bartlett's test tables show that income, education, and potential factors are significant for community welfare in Siheneasi Village, Lahewa District. In contrast, capital, distribution, labor, and technology factors negatively or insignificantly affect the community's welfare in Siheneasi Village, Lahewa District. Moreover, multiple linear regression testing results show partial hypothesis test results for consumption, income, education, and significant potential for community welfare in Siheneasi Village, Lahewa District.